MALONDIALDEHYDE (MDA) SEBAGAI PENANDA STRESS OKSIDATIF PADA TUBUH - Rita Kirana, (Jurnal Cakrawala Ilmiah, 2025)
One biomarker that is often used to measure oxidative stress is Malondialdehyde (MDA). MDA is the end product of lipid peroxidation, which is the oxidation process of unsaturated fatty acids that occurs due to ROS attack on cell membranes. As a degradation product of lipid peroxidation, MDA has the potential to form adducts with various biomolecules such as proteins and DNA, which can cause cellular damage and impaired organ function (Marnett, 1999). Due to its reactive nature and easy detectability in biological samples, MDA is often used in research to measure the extent of oxidative damage and provide a clear picture of the extent to which oxidative stress affects the body. Malondialdehyde (MDA) has proven to be a very useful biomarker for measuring the level of oxidative stress in the body. As a product of lipid peroxidation, MDA provides a clear indication of the damage caused by ROS to cell membranes and other cellular components. Elevated MDA levels are often found in various degenerative diseases and medical conditions associated with oxidative stress, including cardiovascular diseases, diabetes, cancer, and neurodegenerative disorders. Therefore, measurement of MDA levels not only serves as an indicator of oxidative damage, but can also be used as a diagnostic and prognostic tool to monitor disease progression as well as the effectiveness of targeted therapies to reduce oxidative stress